PENEGAKAN HUKUM PIDANA TERHADAP PELAKU TAWURAN PELAJAR OLEH POLISI RESOR KOTA PADANG - Harisul Huda; Erdianto Effendi; Adi Tiara Putri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Seeing the situation and conditions that occur in the city of Padang often brawls between high school students (high school) and or vocational high school (SMK) so that makes researchers interested in reviewing it legally, because these situations and conditions often occur repeatedly. Triggers brawl is usually a sense of revenge, with a high sense of solidarity these students will reciprocate the treatment caused by school students who are considered harmful to a student or defame the school. This paper discusses criminal law enforcement conducted by the Padang District Police against brawlers between students in the Padang City jurisdiction, the obstacles faced by the Padang District Police in carrying out criminal law enforcement efforts against student brawls in the Padang City legal area and efforts made by the Padang City Police in anticipating against student brawlers.The research method is a sociological legal research that is research that wants to see the correlation of law with the community, so that it can reveal the effectiveness of the law in society and identify unwritten laws that apply to the community by jumping directly into the research location. Location of the study in Padang Police, researchers collected data consisting of primary, secondary and tertiary data. Data collection techniques namely questionnaire, interview and literature study. Data analysis was carried out qualitatively and drawing conclusions from the author using deductive thinking methods.The conclusion of this research is that the criminal law enforcement conducted by the Padang District Police against brawl perpetrators between students in the legal area of the City of Padang has not been effectively implemented, while law enforcement can guarantee legal certainty, order and legal protection. The obstacle in upholding criminal law against student brawls in the legal area of Padang City is firstly the lack of adequate means of vehicles to conduct patrols is still very limited, so that the police are still difficult to reach small alleys to monitor conditions that are said to be prone to misbehavior adolescents, secondly the lack of parental supervision of children and thirdly the lack of public trust in law enforcement officials. So that in the future the Padang City government should support the police and the TNI to cooperate in securing and preventing student brawls, so that in the future they can anticipate student brawls in the City of Padang.Keywords: Student - Student Fight - Padang Police Station.